WACANA POLITIK PADA PIDATO ANGGOTA PARLEMEN INDONESIA TENTANG PENANGANAN COVID 19 - Priatna, Achmad Nashrudin (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Communication as the essence of interaction between people plays an important role in all aspects of life, including politics. The view that communication includes politics, presumably understandable, because politics is all-present (ubiquitous) and multi-dimensional. Political communication, in practice can take the form of speech, public speaking or rhetoric. And when it comes to political communication in its various forms, our attention will be drawn to the various colors of the speeches of legislators (in this paper the author mentions lawmakers). There are three indicators analyzed, by using Aristotle's rhetorical theory, namely Ethos, pathos and Logos. This paper uses a qualitative method which is considered as a written analysis of words related to ideas, ideas, beliefs, feelings, habits and behaviors of human Walliman in (Akbar, 2021). The analysis used by the authors is descriptive analytical to provide an overview of how the perspectives of lawmakers (in other terms, legislators) view the functioning of the state and government in the covid 19 vaccination program. Meanwhile, the data analysis technique in writing this article departs from an explanation (Creswell, 2014) which focuses on data analysis through data organization, reading and recording, as well as description, clarification, and interpretation (Agustino, 2020). The result is that MPs' speeches on Indonesia's Covid 19 handling policies are largely determined by their position, whether from government-supporting parties or the opposition